Russia and Turkey between Cooperation and Rivalry - Babayan, Hovsep (ԱԵԳՄՄ հրատ.)
This article discusses the dynamics of relations between Russia and Turkey and particularly the balance of power in the Black Sea and the South Caucasus. The article first aims briefly to describe the bilateral relations of Russia and Turkey after the Cold War and analyze their balance of power relations in the Black Sea and the South Caucasus. For this purpose, the economic and energy cooperation is examined. Then, particularly regional foreign and military policies and their outcomes is analyzed. The author examined qualitative methods (retrospective case study) to reveal the main tendencies of bilateral relations and comparative analysis of power balance relations. Both primary and secondary (academic and expert works) sources have been considered as basis of the research. Հոդվածում քննարկվում են Ռուսաստանի և Թուրքիայի միջպետական հարաբերությունների ընդհանուր բնույթը և միտումները։ Աշխատանքի նպատակն է բացահայտել Ռուսաստանի և Թուրքիայի միջպետական հարաբերությունների դինամիկան Սառը պատերազմի ավարտից հետո, այնուհետև վերլուծել երկկողմ հարաբերությունների ուժային հավասարակշռությունը Սև ծովում ու Հարավային Կովկասում։ Այդ նպատակով խնդիր է դրվել ուսումնասիրել ռուս-թուրքական հարաբերություն– ների առանցքում ընկած տնտեսական ու էներգետիկ հարաբերությունները և վերլուծել երկու տարածաշրջաններում այս երկրների քաղաքականությունը և դրա արդյունքները՝ շեշտը դնելով առաջին հերթին ռազմաքաղաքական հարաբերությունների վրա։ В статье обсуждаются общие черты двухсторонних отношений России и Турции. В частности, целью работы является выявление основных тенденций двухсторонних отношений после Холодной войны и анализ силового баланса в регионах Черного моря и Южного Кавказа. Для этого поставлена задача исследовать экономические и энергетические взаимоотношения двух стран, проанализировать их внешнюю и военную политику и ее результаты в регионах. Для выявления основных тенденций двусторонних отношений и баланса сил использованы качественные методы (ретроспективное тематическое исследование) и сравнительный анализ силового баланса. В исследовании использованы первичные и вторичные (академические и экспертные работы) источники данных, касающиеся русскотурецких отношений.
Keywords: International relations